2018
DOI: 10.5435/jaaos-d-17-00230
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Nerve Injury After Hip Arthroscopy

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
3
24
0
2
Order By: Relevance
“…Kern et al . 15 reported the incidence of nerve injury after hip arthroscopy could be up to 13% and the traction related neurapraxia was underestimated previously. Bailey et al 16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kern et al . 15 reported the incidence of nerve injury after hip arthroscopy could be up to 13% and the traction related neurapraxia was underestimated previously. Bailey et al 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Frandsen et al 14 reported that up to 74% of patients complained of some kind of traction-related problems after hip arthroscopy, and neurapraxia is the most commonly reported. Kern et al 15 reported the incidence of nerve injury after hip arthroscopy could be up to 13% and the traction related neurapraxia was underestimated previously. Bailey et al 16 reported the mean traction time was 46.5 min, and a longer traction time and a greater traction force could result in groin numbness and pudendal neurapraxia.…”
Section: Traction Time and Traction-related Complicationsmentioning
confidence: 99%
“…4 However, patient safety is of paramount importance, and known potential groin complications are what we all try to avoid. 5,6 With removing the post, we eliminate the possibility of iatrogenic groin injury, but we must ask ourselves, is changing our technique necessary? Those already adopting post-free think so, but studies are needed to show safety and efficacy of post-less arthroscopy.…”
Section: See Related Article On Page 2840mentioning
confidence: 99%
“…[1][2][3] Multiple studies have demonstrated that the majority of neuropraxias related to hip arthroscopy affect the pudendal nerve. [2][3][4] In a prospective study performed by Kern et al, 4 the incidence of nerve injury was 13% (13 of 100 patients), with 9 of these patients The patient is positioned supine and a perineal post is placed only for positioning so the patient does not fall off the bed. Once general anesthesia is performed, the patient is moved to the edge of the table on the side of the surgical hip so that the surgeon does not run into the bed with the hand when holding the camera during the surgical case.…”
mentioning
confidence: 99%